Symbiosis of executive and selective attention in working memory - Vandierendonck, André (Frontiers in Human Neuroscience, 2014)
The notion of working memory was introduced to account for the usage of short-term memory resources by other cognitive tasks such as reasoning, mental arithmetic, language comprehension, and many others. This collaboration between memory and other cognitive tasks can only be achieved by a dedicated working memory system that controls task coordination. To that end, working memory models include executive control. Nevertheless, other attention control systems may be involved in coordination of memory and cognitive tasks calling on memory resources. The present paper briefly reviews the evidence concerning the role of selective attention in working memory activities. A model is proposed in which selective attention control is directly linked to the executive control part of the working memory system. The model assumes that apart from storage of declarative information, the system also includes an executive working memory module that represents the current task set. Control processes are automatically triggered when particular conditions in these modules are met.. As each task set represents the parameter settings and the actions needed to achieve the task goal, it will depend on the specific settings and actions whether selective attention control will have to be shared among the active tasks. Only when such sharing is required, task performance will be affected by the capacity limits of the control system involved.